La Révolution mexicaine dans les manuels scolaires français - Véronique Pugibet (Caravelle)
This paper examines the evolution of how the Mexican Revolution is represented in Spanish textbooks in France between 1958 and 2008. It analyzes the relationship among different national programs, the choice of different media in support of memory, and the important role of graphic design. The Revolution still appears as a myth in the 60s, but this image will fall apart little by little due to various reasons.